Persuasive Television Advertising in Bakery Sector - Matellanes Lazo, Mónica (2017)
In recent years, a great diversity of new products has emerged in the sector of children’s pastries, but there are others that have long been in our daily lives. In spite of being more those that have failed than those that are maintained, it is crucial to analyze how its advertising has evolved over time, knowing how to adapt to the tastes of different generations of consumers. There has clearly been a movement of concern and awareness among the customers and consumers about the ingredients that make up the food, and because of the change in attitude and the proliferation of consumer rights associations, there has been an evolution in this type of products, both at the production level and at the communicative level. Through the content analysis of the messages from their spots and a discussion analysis, a comparative study of the same between the years of the eighties and the last years has been made to see their evolution.